UK parliamentary inquiry reports in forensic science – Plus ça change? - Shrey Jhalani; Ruth M. Morgan; Amelia Shooter; John Cassella (Forensic Science International: Synergy)
Forensic Science provision in England and Wales underpins scientific evidence in many criminal cases. The quality of scientific investigation by scientists and the presentation of science insights has been under scrutiny and it is increasingly established that multiple significant, deep-rooted and persistent issues exist in the Forensic Science ecosystem.A thematic analysis of seven UK parliamentary inquiry reports that addressed Forensic Science and published since 2000, identified key themes and contextual factors. A matrix model that illustrates the connectivity between these themes and factors was produced. The primary issue identified was the challenge of the traditionally narrow focus of inquiries on specific elements of the Forensic Science ecosystem, rather than considering that ecosystem holistically.Through the analysis of these seven inquiry reports, it was possible to develop a matrix which provides a structured framework to critically consider the interconnections, interdependencies and connectivity between the key elements of the Forensic Science ecosystem. The matrix serves to highlight the need for an integrated approach that brings together an understanding of each component of the system and their intersections and connections to address the Forensic Science ecosystem more holistically and address the root causes of key Forensic Science challenges within the criminal justice system. It is hoped that the insights identified in this study offer a starting point for broader discussions and strategic activities across the Forensic Science community to find pathways forward to address persistent deep-seated challenges that have been identified in Forensic Science and find solutions.